Income convergence and regional policies in Europe: results and future challenges - Martin Hallet (European Regional Science Association (ERSA), 2002)
A frequently expressed criticism on regional polices in Europe is that they seem to have hardly any effect in view of the little progress in regional convergence over the last two decades. The paper criticises this view for being overly simplistic for several reasons. First, it does not differentiate between the developments in different types of countries. Second, it attributes the income performance of regions exclusively to regional policy expenditure, although several other factors need to be in place in order to have a visible effect in terms of income convergence. Third, concluding from the income performance on the success or failure of policies fails to take into account the counterfactual situation, i.e. it does not properly analyse what would have happened in the absence of these policies. The paper elaborates on these arguments on the basis of stylised facts of regional disparities in Europe, main determinants of income convergence and the role of EU Structural Funds. It concludes by discussing some of the main future challenges of regional policies in Europe.
Keywords: 330